Pengaruh pendekatan pembelajaran masalah terbuka terhadap kemampuan berpikir kreatif matematis siswa - Simangunsong, Laurent (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Mathematical creative thinking is a process of synthesizing ideas, building new ideas and applying them to produce new combinations based on data or information that already exist. The results of interviews with several students showed that students still tend to memorize trigonometric formulas because there are many who consider that the concept of trigonometry is not fully mastered by students, so the learning outcomes obtained are less satisfactory. This study aims to (1) analyzing the application of the steps of the open problem learning approach, and (2) analyzing the level of mathematical creative thinking of students. The data obtained are then described specifically, clearly, and in detail with words to get meaning from the results of research that have been done. Data collection methods include field notes, written tests. The results of this study are: (1) The steps of teaching students are to provide a variety of problem solving, then guide students to develop mathematical concepts and give students the opportunity to solve problems with various solutions or ways, (2) by 60,60% of students meet the very creative category, amounting to 24,24% of students having the less creative category, and of 15,16% of the students having the non-creative category.